Information and communication technologies in the development of students' foreign language competence - Volkova, G. K.; Wieler, G. O.; Волкова, Галина Костянтинівна; Вілер, Ганна Олександрівна (My University, 2022)
Students majoring in nonlinguistic subjects have to master a foreign language for general and professional use. Demands of the present day society challenge the possibilities of modern higher education and call for the need to find new methods and means of training future specialists. The concept of personally oriented education involves the introduction of innovative methods and forms of organization of students' educational and cognitive activities into the educational process. One of the effective ways to implement personally-oriented learning is the efficient use of information and communication technologies (ICT)